THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND BURNOUT AMONG EFL UNIVERSITY STUDENTS: A CASE STUDY - Hadil Dahia; Yasmine Mouloudj; Imane Fersaoui (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The present study seeks to explore the relationship between Algerian EFL students’ emotional intelligence (EI) and their burnout status. To determine the levels of these variables and reach the purpose of the study, two self-report scales are employed with a sample of 57 EFL third-year students at Ecole Normale Supérieure of Bouzareah (ENSB), in Algiers. The first scale is the Brief Emotional Intelligence Scale (BEIS-10), used to measure the students’ EI level, while the second one is the Maslach Burnout Inventory–Student Survey (MBI-SS), used to measure their burnout level. Surprisingly, the findings reveal no significant relationship between the EI level of EFL students and their burnout level since the Pearson’s Correlation demonstrates that r= .024, which suggests that EI is not a factor that affects burnout. The results also show that 60% of the students have a high level of EI, and 40% have a high level of burnout.